Seed production of Moringa oleifera Lam cultivars in Cauto Valley - Ledea Rodríguez, José Leonardo (2018)
Moringa oleifera has shown innumerable benefits as animal feed. For the expansion of this plant, a largeamount of quality seeds is necessary and, to produce them, sowing density and the cultivars used must be considered, among other factors. The objective of this work was to determine the effect of sowing distance on seed yield of four moringa cultivars. The study was carried out at the Experimental Pasture and Forage Station Pastures and Forages (EEPF, in Spanish) of the Institute of Agricultural Research(IIA, in Spanish) “Jorge Dimitrov” in Bayamo, Granma, Cuba. Four cultivars: Plain, Nicaragua, Supergenius, and Criolla, were evaluated on a Fluvisol soil in Cauto Valley. Twelve treatments, combining cultivar and sowing distance: 3x1, 3x2, and 3x3 m, were applied. The variables stem thickness, branches per plant,fruits per plant, fruit length, seeds per plant, and seed yield per plant and per hectarewere measured. There was not a significant interaction between cultivar and sowing distance for the studied variables.The best response of yield components was obtained from plants spaced at 3x2 and 3x3 m; however, the highest yield per hectare were reached from plants spaced at 3x1 and 3x2 m. Cultivarr was significant (p≤0.05) on stem thickness, fruit length, and seeds per fruit. For sowing distance, the significant variables (p≤0.05) were: stem thickness, branches and fruits per plant as well as yield per plant and per hectare.